HUBUNGAN PEMAHAMAN TEKS EKSPOSISI DENGAN KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS VIII SMP PGRI PEKANBARU - Prasasti, Wahyuni; Auzar, Auzar; Burhanudin, Dudung (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research entitled the correlation understanding of exposition text with exposition text writing skills of VIII grade students of Junior High School PGRI Pekanbaru. This research aims to describe the correlation understanding of exposition text and writing skills exposition text of VIII grade students of Junior Highh School PGRI Pekanbaru. This type of research is quantitativeresearch with descriptive methods. The data of this study arein the form of an objective test score understanding of exposition text with the performance test scores writing skills in exposition text writing sjkills for VIII grade students of Junior High School PGRI Pekanbaru. The results of the reserach were found (1) understanding of the exposition text of class VIII Pekanbaru PGRI Middle School students was in sufficient qualification (63.40) and had not yet fulfilled the KKM (63.40 <80.00), (2) exposition text writing skills of junior high school students PGRI Pekanbaru is in sufficient qualification (59.85) and has not fulfilled KKM (59.85 <80.00), and (3) there is a significant correlation between understanding of the exposition text and the writing skills of exposition text of class VIII students of Junior High School PGRI Pekanbaru degree of freedom n-1 and significant level of 95%. Key Words: correlation, understanding, writing skill, exposition text.